Levofloxacin versus placebo for the treatment of latent tuberculosis among contacts of patients with multidrug-resistant tuberculosis (the VQUIN MDR trial): a protocol for a randomised controlled trial. Issue 1 (2nd January 2020) - Fox, Greg J; Nguyen, Cam Binh; Nguyen, Thu Anh; Tran, Phuong Thuy; Marais, Ben J; Graham, Steve M; Nguyen, Binh Hoa; Velen, Kavi; Dowdy, David W; Mason, Paul; Britton, Warwick J; Behr, Marcel A; et al.
Abstract : Introduction: Treatment of latent tuberculosis infection (LTBI) plays a substantial role in the prevention of drug-susceptible tuberculosis (TB). However, clinical trials to evaluate the efficacy of preventive therapy for presumed multidrug-resistant (MDR) LTBI are lacking. This trial aims to evaluate the efficacy of the antibiotic levofloxacin in preventing the development of active TB among latently infected contacts of index patients with MDR-TB. Methods and analysis: A double-blind placebo-controlled parallel group randomised controlled trial will be conducted in 10 provinces of Vietnam. Household contacts living with patients with bacteriologically confirmed rifampicin-resistant or MDR-TB will be eligible for recruitment if they have a positive tuberculin skin test or are known to be immunosuppressed, and do not have active TB. Participants will be randomised to receive either levofloxacin or placebo tablets once per day for 6 months. Screening for incident TB will be performed at 6 months intervals. The primary study outcome is the incidence of bacteriologically confirmed TB within 30 months after randomisation. Analysis will be by intention to treat, using Poisson regression. Ethics: Ethical approval from the University of Sydney Human Research Ethics Committee was obtained on 29 April 2015 (2014/929), and from the Vietnam Ministry of Health Institutional Review Board on 30 September 2015 (4040/QD-BYT). Dissemination: Findings of the study will be published in peer-reviewed publications and conference presentations. Trial registration number: ACTRN12616000215426.